Optimizing MR-Guided Radiotherapy for Breast Cancer Patients - Groot Koerkamp, Maureen L.; Vasmel, Jeanine E.; Russell, Nicola S.; Shaitelman, Simona F.; Anandadas, Carmel N.; Currey, Adam; Vesprini, Danny; Keller, Brian M.; De-Colle, Chiara; Han, Kathy; Braunstein, Lior Z.; Mahmood, Faisal; et al. (Frontiers in Oncology, 2020)
Current research in radiotherapy (RT) for breast cancer is evaluating neoadjuvant as opposed to adjuvant partial breast irradiation (PBI) with the aim of reducing the volume of breast tissue irradiated and therefore the risk of late treatment-related toxicity. The development of magnetic resonance (MR)–guided RT, including dedicated MR-guided RT systems [hybrid machines combining an MR scanner with a linear accelerator (MR-linac) or 60Co sources], could potentially reduce the irradiated volume even further by improving tumour visibility before and during each RT treatment. In this position paper, we discuss MR guidance in relation to each step of the breast RT planning and treatment pathway, focusing on the application of MR-guided RT to neoadjuvant PBI.